ASSESSMENT OF BACKGROUND IONIZING RADIATION LEVEL OF SCRAP METAL DUMPSITES IN DUTSE TOWN, JIGAWA STATE, NIGERIA. - DANKAWU UM; G.D, ADAMU; M.N, MAHARAZ; SHARFADDEEN, M.M; USMAN, I.Z; S.O, OLAMBIMTAN; H. Y. SHUAIBU; S.S. ZARMA; A.G, ASHIRU; F.M, USMAN; CHIFU, E (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The level of awareness of the radiation hazards from indiscriminate dumping of scrap metals is very low in developing countries. In this study, the background ionizing radiation level of scrap metal dumpsites in Dutse Town, Jigawa State, Nigeria was assessed. A hand-held Radiation Alert Inspector (RAI) was used and a total of Ten (10) scrap metal dumpsites were randomly selected. Four readings were taken in Counts Per Minute (CPM) and micro Sievert per hour(μSv/hr) at four (4) different selected points on each of the dumpsites. The value of exposure dose rate (in μSv/hr) was used to estimate the Absorbed Dose D (in nGy/hr), Annual Effective Dose (in mSvy-1) and Excess Lifetime Cancer Risk respectively. The results show that the mean exposure dose rate range from 0.01225 to 0.02125 μSv/hr. All the values of exposure dose rate were found to be below the standard value of 0.133 μSv/h. The mean value of the Absorbed Dose D varies from 12.25 to 21.25 nGy/hr respectively. The calculated mean Annual Effective Dose was found to be in the range of 0.015023 to 0.026061 mSvy-1. These values are below 1.0 mSvy-1 dose limit recommended by the International Commission on Radiological Protection (ICRP). The mean Excess Lifetime Cancer Risk range from 0.052582 to 0.091214 and are lower than the world limit of 0.29 × 10-3. The study indicates that the people working and living within the study area are safe and are not exposed to high doses of radiation as result of activities in the dumpsite. However, continuous monitoring of background radiation in the dumpsites is recommended.